FINANCIAL MANAGEMENT IN FOOD ENTERPRISES AND GLOBALIZATION OF ELECTRONIC BUSINESS IN SERBIA - D. Mičić, Ivan; Totić, Ibrahim; Halilagić, Ahmet (Economics of Agriculture, 2018)
Use of finance in a certain form has been present and operational since the emergence of the worlds first civilizations such as: Egypt, Greece, Babylon, Rome and others. At that time, however, the financial system was primarily based on archaic stores of value - gold or silver money. In its basic definition, finances were created with the concept of money and the development of its functions as a payment and transactional mechanisms. Where there is no money, there is no value. Money is the determinant, but also the function of finance. The development of finance as a science and its function relates to the emergence of the state, since it is the primary creator and backer of money. In this regard, public-state finances first began to be studied, followed by other financial disciplines. Whereby the equilibrium arises from the payment of debt, collection of claims between states, enterprises and individuals.